Managing alcohol-related problems among Indigenous Australians: what the literature tells us - Gray, Dennis; Saggers, Sherry; Wilkes, Edward; Allsop, Steve; Ober, C. (Blackwell Publishing Asia, 2010)
Objective: To contextualise and provide an overview of two review papers – prepared as part of a larger research program – dealing with different aspects of the treatment of Indigenous Australians with alcohol-related problems. Method: The papers were reviewed thematically and compared to identify key issues raised in them. Findings: Together, the papers highlight the paucity of the evidence base for the provision of treatment for Indigenous Australians with alcohol-related problems. Among the key issues identified are: the need to engage with clients in culturally safe ways; practitioner, organisational and client barriers to engagement; the contexts in which Indigenous drinking and treatment take place; the need to develop rigorous methods of evaluation more appropriate to Indigenous cultural and service provision settings; and the importance of effective partnerships in the provision of services. Conclusion: For those working in the field, the reviews direct attention to the need to review and interrogate our current practice. They also provide clear directions for future research.